A study on existing masonry heritage building to explosive-induced blast loading and its response. (3rd August 2021) - Anas, S.M.; Ansari, Md. I.; Alam, Mehtab
In the present study, explicit dynamic analysis has been conducted to investigate the blast response of the masonry heritage building, located in the southern part of Asia, subjected to peak overpressures generated from the TNT charges at different standoff distances and locations. The explosive-induced blast wave pressure-time history has been modelled using the modified Friedlander's equation for different scaled distances. For safety and security purpose varying explosive charges have been concealed in this investigation. A sophisticated material model available in the ABAQUS/CAE program has been utilised to compute damage dissipation energy and distribution of damage for the considered locations of the varying explosive charges. The stress analysis results have been compared with the provisions of the Indian Standard Code of Practice for Structural Use of Unreinforced Masonry, IS 1905(1987). This study shall open a new vista for engineers and researchers working in the field of blast engineering.